Aldehyde dehydrogenase-2 protects against myocardial infarction-related cardiac fibrosis through modulation of the Wnt/β-catenin signaling pathway - Zhao XJ; Hua Y; Chen HM; Yang HY; Zhang T; Huang GQ; Fan HJ; Tan ZB; Huang XF; Liu B; Zhou YC (Dove Medical Press, 2015)
Xinjun Zhao,1,2,* Yue Hua,1,2,* Hongmei Chen,1,2,* Haiyu Yang,3,* Tao Zhang,1,2,* Guiqiong Huang,4,* Huijie Fan,1,2 Zhangbin Tan,1,2 Xiaofang Huang,1,2 Bin Liu,5 Yingchun Zhou1,21The Key Laboratory of Molecular Biology, State Administration of Traditional Chinese Medicine, School of Traditional Chinese Medicine, Southern Medical University, Guangdong, Guangzhou, People’s Republic of China; 2Nanfang Hospital, Southern Medical University, Guangdong, Guangzhou, People’s Republic of China; 3Jiangmen Wuyi Traditional Chinese Medicine Hospital, Guangdong, Jiangmen, People’s Republic of China; 4Huizhou Hospital of Traditional Chinese Medicine, Huizhou, People’s Republic of China; 5The Second Affiliated Hospital of Guangzhou Medical University, Guangdong, Guangzhou, People’s Republic of China*These authors contributed equally to this workBackground: Aldehyde dehydrogenase-2 (ALDH2) has a protective effect on ischemic heart disease. Here, we examined the protective effects of ALDH2 on cardiac fibrosis through modulation of the Wnt/ß-catenin signaling pathway in a rat model of myocardial infarction (MI).Methods: Wistar rats were divided into the sham (control), MI (model), and ALDH2 activator (Alda-1) groups. After 10 days of treatment, the left ventricular (LV) remodeling parameters of each animal were evaluated by echocardiography. Myocardial fibrosis was evaluated by Masson’s trichrome staining and Sirius Red staining. Expression levels of collagen types I and III and β-smooth muscle actin (α-SMA) were examined. Finally, the expression and activity of ALDH2 and the levels of several Wnt-related proteins and genes, such as phospho-glycogen synthase kinase (GSK)-3β, GSK-3β, β-catenin, Wnt-1, WNT1-inducible signaling-pathway protein 1, and tumor necrosis factor (TNF)-α, were also analyzed.Results: After MI, the heart weight/body weight ratio, LV dimension at end diastole, and LV dimension at end systole were decreased, while the LV ejection fraction and LV fractional shortening were increased in the Alda-1 group. Myocardial fibrosis was also reduced in the Alda-1 group, accompanied by decreased expression collagen types I and III and α-SMA. β-Catenin, phosphorylated GSK-3β, and Wnt-1 levels were significantly increased in the model group. Interestingly, this alteration was partly reversed by Alda-1 treatment. Immunohistochemical staining showed that numerous WNT1-inducible signaling-pathway protein 1 (WISP-1)- and TNF-α-positive cells were found in the model group. However, few WISP-1- and TNF-α-positive cells were detected in the Alda-1 group.Conclusion: The reduction of cardiac fibrosis and the down-regulation of β-catenin, phosphorylated GSK-3β, Wnt-1, and WISP-1 may be mediated by increased ALDH2 activity, leading to reduction of MI-related cardiac fibrosis.Keywords: myocardial infarction, aldehyde dehydrogenase, cardiac fibrosis, Wnt signaling